SISTEM INFORMASI DATA VAKSIN DAN PAKAN AYAM PADA PT. TELUR SUKSES SEJAHTERA SEBAPO II MENGGUNAKAN SCAN BARCODE: System, Information, Chicken Feed and Vaccine Data, Microsoft Visual Basic 6.0, Microsoft Access and Crystal Report. - Suana, Irma; -, Nilawati (JURNAL AKADEMIKA, 2020)
Chicken Vaccine and Feed Data Information System is a system that provides information services in the form of Chicken Vaccine and Feed Data information systems to the public. The existence of this information system is important. In this case, PT. Telur Sukses Sejahtera Sebapo II is used as a research site, because the Chicken Vaccine and Feed Data information system in that place has not been managed properly so that errors often occur in making reports, such as processing data calculation of the amount of feed stock and processing of vaccine stock data. This research is to minimize errors in the Chicken Feed and Vaccine Data report. The research method used Research and Development (R&D) method. The analytical tool used Data Flow Diagrams (DFD). The software used : Microsoft Visual Basic 6.0, Microsoft Access, and Crystal Report 8.5. This information system was built to provide convenience in processing feed and vaccine data as well as processing feed and vaccine data reports to make it more precise and accurate.